Biko: A Portrait in Words - M-Afrika, Andile (WritingThreeSixty, 2018)
I Write What I Like by Steve Biko was published 39 years ago. The book consists of writings that were written by Biko almost 47 years ago. Instrumental behind the publication of the book was Fr Aelred Stubbs CR, who knew Biko and who wanted to pay tribute to him. Like many, Fr Stubbs was disturbed by the cruel manner in which Biko was murdered by the apartheid regime. I Write What I Like, therefore, was meant to keep Biko’s memory alive.